2016
DOI: 10.1002/jnr.23860
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender on corticotropin‐releasing factor and noradrenergic sensitivity in cocaine use disorder

Abstract: Responses to stress may be important in understanding sex and gender differences in substance use disorders and may also be a target for development of treatment interventions. A growing body of both preclinical and clinical research supports important underlying sex and gender differences in the corticotropin releasing factor (CRF) and noradrenergic systems, which may contribute to drug use. Preclinical models have demonstrated increased sensitivity of females as compared to males to CRF and noradrenergic-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 85 publications
0
6
0
1
Order By: Relevance
“…HR elevations occur immediately after exposure to a stressor and are regulated the locus-coeruleus-noradrenergic (LC-NE) sympathetic nervous system, which is rapidly mobilized following stress. There is a robust literature suggesting increased sensitivity of the noradrenergic system in women with cocaine (McRae-Clark et al, 2017) and tobacco (McKee et al, 2015) use disorders as compared to men. For example, women with cocaine use disorder exhibit more physiologic response and anxiety when administered yohimbine, an agent that increases NE release (Moran-Santa Maria et al, 2014) and more diminution of craving and stress response following administration of an agent that decreases noradrenergic function (Fox et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…HR elevations occur immediately after exposure to a stressor and are regulated the locus-coeruleus-noradrenergic (LC-NE) sympathetic nervous system, which is rapidly mobilized following stress. There is a robust literature suggesting increased sensitivity of the noradrenergic system in women with cocaine (McRae-Clark et al, 2017) and tobacco (McKee et al, 2015) use disorders as compared to men. For example, women with cocaine use disorder exhibit more physiologic response and anxiety when administered yohimbine, an agent that increases NE release (Moran-Santa Maria et al, 2014) and more diminution of craving and stress response following administration of an agent that decreases noradrenergic function (Fox et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the previously documented exaggerated response to spinal anaesthesia in females, [19][20][21][22] the effectiveness of NE infusion for maintaining blood pressure with associated greater heart rate and cardiac output than with phenylephrine during SA for Caesarean section, as documented in the literature, [23][24][25] could be considered as support for the results of the current study.…”
Section: Discussionmentioning
confidence: 68%
“…These are considered limitations, since gender differences in CRH reactivity have been demonstrated. 29,30 In these studies, women were shown to be more sensitive to stimulation than men. In the present study, 19 of 20 subjects were men.…”
Section: Discussionmentioning
confidence: 99%